The World Bank Group in the West Bank and Gaza, 2001-2009 : Evaluation of the World Bank Group Program - Independent Evaluation Group (Washington, DC: World Bank, 2015)
This evaluation assesses the outcomes of World Bank Group’s (WBG’s) development support to the West Bank and Gaza for the period 2001-09. It covers the programs of the World Bank - International Bank for Reconstruction and Development (IBRD), International Development Association (IDA), International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA). The main objectives of the WBG program were broad, reflecting the extremely volatile political situation, characterized by frequent humanitarian and economic crises that required abrupt shifts in the Bank’s strategy. The WB is both the main economic adviser to the Quartet on the Middle East and the administrator of large donor trust funds. The WBG made important contributions in identifying obstacles to development, estimating their costs, and promoting the search for reasonable compromises. The Bank Group program needs to recognize that the long-term development effectiveness of its support is heavily dependent on the Israeli-Palestinian political framework, as well as close alignment of its efforts with those of other donors. Other specific recommendations of this evaluation include: developing a medium-term strategy with a focused results framework; exploring opportunities for closer cooperation with Arab donors; helping the Palestinian Authority (PA) to develop a long-term strategy to reduce aid dependence; and identifying opportunities for Israeli-Palestinian cooperation on different aspects of development.